Archeologia dello spirito - Ferraris, Maurizio (Filosofia Morale/Moral Philosophy, 2023)
According to a famous saying, the deepest, in the human, is the surface, the skin; in my view, the deepest and most decisive is the interaction between that skin and a technical apparatus, be it a stick or a smartwatch, and the sense of that interaction generates the archaeology of what, later, may be described and understood as the phenomenology of spirit. In this article I trace the genetic stages of the process by proposing a radical externalism that stems from the conception of the human as an organism systematically connected with techno-social mechanisms.